Which are the leading journals in Human Resources Management and Operations Management in the Web of Science and Scopus databases? Design and application of a classification method - Tamara Boronat-Soler (WPOM : Working Papers on Operations Management)
The aim of this project is to analyze and classify in subareas the journals of the D15 field of ANECA which are in JCR and Scopus simultaneously. This classification will be performed identifying and defining the set of management subareas applying the classification of several sources. Subsequently, the journals will be searched in JCR and Scopus and an unified list will be created. The resulting list will be classified analyzing the content of the web page information and if required, analyzing the topic of the last two articles of published. Finally, the classification obtained will be compared with the one offered by JCR and Scopus.